2018
DOI: 10.1080/15592324.2018.1469361
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the impacts of two different modes of salicylic acid application on tomato (Solanum lycopersicum) responses to salinity

Abstract: Exogenous application of salicylic acid may improve tolerance to salinity. To investigate whether exogenous salicylic acid application had similar protective effects when applied as a priming agent or concomitantly with NaCl, tomato seedlings primed or not with 10 µM salicylic acid were further treated with 125 mM NaCl, 10 µM salicylic acid or combined treatments. Both priming and concomitant application of salicylic acid increased plant growth of salt-stressed plants but their positive impact was not additive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 45 publications
3
31
1
Order By: Relevance
“…Foliar pretreatment with SA was the most effective method of SA application to recover plant growth under salinity. Similar results indicating the better effect of leaf pretreatment with SA have been also reported [13,27,32,36]. Despite roots are the first organ to face saline ions; however, leaves are the main and final target of toxic ions of salinity.…”
Section: Comparison Of the Different Modes Of Sa Applicationsupporting
confidence: 85%
See 1 more Smart Citation
“…Foliar pretreatment with SA was the most effective method of SA application to recover plant growth under salinity. Similar results indicating the better effect of leaf pretreatment with SA have been also reported [13,27,32,36]. Despite roots are the first organ to face saline ions; however, leaves are the main and final target of toxic ions of salinity.…”
Section: Comparison Of the Different Modes Of Sa Applicationsupporting
confidence: 85%
“…In another study, seed soaking or foliar pretreatment of SA provided similar tolerance effect in muskmelon under drought stress conditions [26]. In tomato plant, it has been shown that foliar application of SA generally induces tolerance to salinity stress [13,30]; however, seed soaking (priming) and root feeding of SA revealed contradictory results [8,30,37]. Application of 1 mM SA in nutrient solution of tomato plants reduced stomata conductance, CO 2 fixation and photosynthesis rates, resulting in the death of tomato plants [37].…”
Section: Introductionmentioning
confidence: 87%
“…about the importance of the concentration of SA used for improve seed treatment according to the species studied. In tomatoes, Hayat et al (2008) found that plants subjected to water limitation were benefited by the application of SA of 10 µM, Senaratna et al (2000) showed that concentrations between 100-500 µM of SA induced a tolerance to multiple stresses, Gharbi et al (2018) improved tolerance to salt stress using 10 µM of SA. In none of these studies was applied seed priming with SA and water limitation simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, positive correlation between salinity tolerance and K + retention have been evidenced in many salt sensitive plants like alfalfa ( Guo et al, 2016 ), mustard ( Chakraborty et al, 2016 ), wheat ( Wu et al, 2015 ), cucumber ( Redwan et al, 2016 ) and cotton ( Wang et al, 2017 ). It was suggested that Na + absorption pathway is highly dependent on K + channels and K + homeostasis under high NaCl concentration in wild species could be attributed due to tolerate high Na + endogenous concentration ( Gharbi et al, 2018 ). In a recent study, demonstrated the osmotic adjustment response of S. lycopersicum and S. chilense under 125 mM salt stress for 7 days, and reported contrasting behavior in the two with respect to modalities of osmotic adjustment and phyto-hormonal profiling.…”
Section: Discussionmentioning
confidence: 99%